Short tandem repeats genotyping of gestational choriocarcinoma - our experiences - Lajos Gergely; Vanda Repiska; Robert Petrovic; Miroslav Korbel; Ludovit Danihel; Jozef Sufliarsky; Michaela Kubickova; Helena Gbelcova; Petra Priscakova (Elsevier, 2024)
Objective: This short communication demonstrates how short tandem repeat genotyping can identify the origin of gestational choriocarcinoma. Materials and methods: The origin of gestational choriocarcinoma in our three cases was determined using the short tandem repeats genotyping technique, which involved quantitative fluorescent PCR and fragmentation analysis. Results: In Case 1 despite no medical history of molar pregnancy, DNA analysis indicated that the choriocarcinoma originated from a homozygous complete hydatidiform mole. We conclude, that the patient's complete abortion 10 years prior to the choriocarcinoma diagnosis was an undiagnosed complete hydatidiform mole. In Case 2 and Case 3 the clinically presumed origin of choriocarcinoma was confirmed. Conclusion: Determining the origin of choriocarcinoma is essential for clinical application, as it affects the FIGO scoring system for gestational trophoblastic neoplasia, which determines the patient's prognosis and treatment approach.